Compensation structure and product market competition - Abowd, John M. 1951-; Allain, Laurence (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1996)
The inability to measure the opportunity cost of labor has plagued analyses of firm-level compensation policies for many years. Using a newly constructed data set of French workers and firms, we estimate the opportunity cost of the employees' time based on a measure of the person-effect in the wage equations (derived from Abowd, Kramarz and Margolis 1994). We then make direct calculations of the quasi-rent per worker at each firm and the conditions within that firm's product market, as measured by international prices, using a representative sample of private French firms. We find that quasi- rents per worker are only mildly related to the structure of the French product market. The systematic variation in our quasi-rents is related to international market prices and work force structure, however, producing an estimate of bargaining power for the employees of about 0.4. This estimate, while slightly larger than other estimates, may be quite reasonable for the workers in an economy in which the vast majority of jobs are covered by industry-level collective bargaining agreements.